Variation of total phosphorus concentration and loads in the upper Yangtze River and contribution of non-point sources - Qian Li (IWA Publishing, 2021)
Excessive phosphorus has become the primary reason for the deterioration of the water quality of the upper Yangtze River Basin. Here, we comprehensively study variations in total phosphorus (TP) concentration and TP loads in the upper reach of the Yangtze River during 2004–2017 (after the impoundment of the Three Gorges Dam). Non-point source TP loads flowing into the mainstream are also analyzed based on the base flow segmentation method. TP concentration in the mainstream showed a fluctuating trend of decreasing–increasing–decreasing from 2004 to 2017. TP loads from tributaries had a greater impact on TP concentration in the mainstream than the retention effect. Non-point source was an important source of TP loads. Average TP loads from non-point source pollution were 24.9 × 106 kg per year, contributing about 50.8% of the TP loads from 2004 to 2017. Non-point source TP loads were mainly from Jinsha River and Jialing River, accounting for 59.1% of total non-point TP loads, and they mainly occurred in the wet season. The long-term variation trend of TP loads from tributaries was affected by economic development, intensity of pollution control and significant discharge change. In terms of pollution control, we suggest comprehensive treatment of point and non-point source pollution. HIGHLIGHTS TP concentration of mainstream showed a trend of decreasing–increasing–decreasing.; TP loads from tributaries had a greater impact on TP concentration in the mainstream than the retention effect.; Average TP loads from non-point source pollution contributed about 50.8% of total TP loads.; Long-term variation trend of TP loads was affected by economic development, intensity of pollution control and significant discharge change.;